Analysis of the Relationships between Mean Red Blood Cell Vol-ume, Red Blood Cell Distribution Width and Hypotension in Patients with Hemodialysis - Jiayong Xie (Tehran University of Medical Sciences, 2021)
Background: We aimed to explore and analyze the relationships between mean corpuscular volume (MCV), red blood cell distribution width (RDW) and hypotension in patients with hemodialysis.